In-vivo antimalarial assessment and toxicity evaluation of elettaria cardamomum seed oil in trypanosoma evansi-induced mice - Baba, Mohd Shukri; Ruslan, Muhammad Safwan (2018)
Elettaria cardamomum is widely applied as alternative medicine and in ethnopharmacological studies. This study was done to evaluate the antimalarial properties of Elettaria cardamomum seed oil against Trypanosoma evansi. The groups of male ICR mice were intraperitoneally (i.p) infected with 0.1 mL of 1 x 105 parasitized red blood cells (RBC) before being orally given pre- and post-infection treatments with 0.2 mL of 100 mg/kg body weight (bw) of E. cardamomum seed oil. By using Giemsa stained, the thin blood smear was microscopically examined and measured. There was a positive correlation (p≤0.05, n = 6) for all assessed parameters; parasitemia density (%), survival time (day) and the ability to inhibit the parasite growth (%) between pre-treated infected mice with the other groups. However, the value recorded was still lower compared with the mice treated with commercial Berenil. Somehow, the results for biochemical tests were positively situated in the normal ranged level. Histologically, no abnormalities and injuries found on the selected vital organs. This study significantly evidenced that Elettaria cardamomum seed oil could be manipulated as a potential antimalarial alternative drug for the preservation and welfare of human beings.